A Study on the Impact of COVID - 19 on Alternative Investment Funds in India - Mangala Minutha, V.; Jagannathan, Uday Kumar (Indian Journal of Research in Capital Markets, 2022)
This paper aimed to study and analyze the four major aspects of the COVID – 19’s effect on alternative investment funds in India. First of all, the research was carried out to study the significant differences between the SEBI quarterly AIF commitments raised in the pre and post covid periods (i.e. from 2018 to 2021) by employing a one-way ANOVA test. The results revealed there existed a statistically significant difference in the AIF structure pre and post COVID - 19. The second aspect involved ascertaining the correlation coefficients between stock market performance and various categories of AIF. It was observed that there was a pattern between BSE 500 and AIF data, suggesting a direct relationship between stock market performance and AIF commitment raised. It was also concluded that Indian interest rates were negatively correlated and the USD/INR rates were positively correlated with the AIF. Further, in the third aspect of the study, primary research was undertaken to understand the investor perception of AIF. For the same, a 23-Likert scale questionnaire was developed for institutional investors and high net-worth individuals who invested in AIF. Finally, out of the five independent variables, four components were extracted using a rotated component matrix. The final aspect of the study focused on crowdfunding. The results indicated that crowdfunding, inherently, may cause the initial agreement to collapse, leaving both parties worse off, that is, VC without a project and the entrepreneur without the VC's expertise. In essence, the study concluded that alternative investment funds were not much affected due to the pandemic. Rather, as an implication, they necessitate a specialized and transparent regulatory framework as an individual asset class.